West Nile Virus Induced Cell Death in the Central Nervous System - Bi-Hung Peng; Tian Wang (Pathogens, 2019)
West Nile virus (WNV), a mosquito-borne, single-stranded flavivirus, has caused annual outbreaks of viral encephalitis in the United States since 1999. The virus induces acute infection with a clinical spectrum ranging from a mild flu-like febrile symptom to more severe neuroinvasive conditions, including meningitis, encephalitis, acute flaccid paralysis, and death. Some WNV convalescent patients also developed long-term neurological sequelae. Neither the treatment of WNV infection nor an approved vaccine is currently available for humans. Neuronal death in the central nervous system (CNS) is a hallmark of WNV-induced meningitis and encephalitis. However, the underlying mechanisms of WNV-induced neuronal damage are not well understood. In this review, we discuss current findings from studies of WNV infection in vitro in the CNS resident cells and the in vivo animal models, and provide insights into WNV-induced neuropathogenesis.